Development of exhibition cabinet - Mohd Afizan, A Ripin @ Ariffin (2007)
Exhibition plays a significant role to make people know about new technology, new product, new development and etc. Cabinet are widely used in exhibition for display. In this project Exhibition Cabinet is developed to improve the commercial design. It is intended to generate a new concept of cabinet that would make display and keep or store a small and light trophy and plague. This involves the process of designing the cabinet by considering the shape and also the ergonomic factor for people to use. After the design has completed, it was transformed to its real product where the design is used for guideline. Several methods and processes involved are conceptual design, material selection, cutting, drilling, welding and finishing. After all the process had been done, this cabinet may help us to understand the fabrication and designing process that involved in this project.